(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Through the contextual analysis of the archaeological record, and from a conceptual and theoretical framework within the idea of liminality is revised, we propose the rethinking and reinterpretation of the archaeological findings spatially related to walls and thresholds of the ‘castros’: human remains, animal and metallic deposits, and sculptured elements such as heads and the so-called ‘Lusitanian warriors’. This paper offers an ap- proach to the symbolic dimension of the walled structures that delimitated the Iron Age settlements of the Iberian Northwest, and it states the existence of magic-religious rituals aimed to sacralised and strengthen the prophylactic character of those liminal places.